Comparative evaluation of public transport systems - Bachok, Syahriah; Paiman, Tuminah; Mohd Maksid, Noor Hafiza; Yaacob, Noor Alyani; Abdul Razak, Sarah; Mohamed Osman, Mariana (2011)
The study focuses on the public transportation systems provided in three different cities: Singapore, Melbourne and Adelaide. Trip details and public transport systems' attributes were recorded in travel diaries. A comparative study was conducted to identify major similarities and characteristics of the public transport systems from the perspective of different user types namely: frequent travellers and first time users. It was found that after the second trips, most of the first time users were getting familiarized with, among others, the ticketing and routing systems. Qualitative evaluation of seven characteristics of public transport systems was undertaken. Elements such as routes, stations and platform identifications, feeder services coverage, number of transfer or interchanges, seamless transfer or interchanges experiences, single or integrated ticketing systems, existence of free city-circle services, complementary versus competitive feeder services and differences of completing trips for familiar routes or destinations compared to trips for unfamiliar routes or destinations were recorded, transcribed and assessed so as to distinguish the variations of trip making processes between first time users and frequent travellers.